Exploring how and why people who drink alcohol at high-risk levels use alcohol-free and low-alcohol drinks when cutting down: a qualitative focus group study - Parvati Perman-Howe; Laura Fenton; Rachel O’Donnell; Rebecca Howell; Inge Kersbergen; Zoe Clarke; John Holmes (BMC Public Health, 2026)
Abstract Background Alcohol-free and low-alcohol drinks are becoming increasingly popular in high-income countries. However, there is limited evidence on their use among general population samples. Drawing on social practice theory, this study aimed to examine how and why people who drink at high-risk levels embed alcohol-free and low-alcohol drinks into their everyday practices when trying to reduce their alcohol consumption. Methods Four online focus groups were conducted with a total of 31 adults from England and Scotland who had made at least one attempt to reduce their high-risk alcohol consumption in the previous 12 months. Data were analysed using reflexive thematic analysis, applying a combination of an a-priori deductive coding framework and inductive coding based on the data. Eight of the 31 participants were ultimately excluded from the final thematic analysis as these participants consistently provided minimal or non-substantive contributions. Consequently, the data come from 23 participants. Results Three overarching approaches were identified. The first was adopted by participants who mostly consume soft drinks at home but find the material resemblance between alcohol-free and low-alcohol drinks and standard alcoholic drinks allows them to replicate drinking rituals in social events outside the home, evoking meanings of friendship, belonging, celebration and fun. The second approach involves participants who integrate alcohol-free and low-alcohol drinks into routine practices at home (e.g. watching TV, reading), but struggle with diverse pressures to consume alcohol during socially-driven or intoxication-oriented practices. The third approach involves participants who find alcohol-free and low-alcohol drinks conflict with their established drinking practices and perceive them as ‘bad value’ due to their lack of alcohol, poor taste and high cost. Conclusion Use of alcohol-free and low-alcohol drinks in attempts to reduce alcohol consumption may operate differently among consumers depending on perceptions of their material properties and their fit with key elements of individuals’ pre-existing drinking practices.